#TITLE_ALTERNATIVE# - AYUDA MAHARSI (NIM : 12209062), DARA
A gas-condensate is a single-phase reservoir fluid that may form condensate in reservoir at certain temperature and pressure. The amount of liquid phase present is also dependent on the composition of the fluid. Due to this behavior, reservoir simulation using black-oil and compositional model will yield different results. Theoretically, compositional model is suitable to perform compositional changing in reservoir condition, such as gas-condensate fluid. However, black-oil model became more applicable if we consider its simplicity and low CPU time in simulation. Unfortunately, black-oil model results may deviate significantly from compositional model during simulation, including gas-condensate reservoir simulation. Therefore, the failure criteria of blackoil model in simulating gas-condensate reservoir should be determined. Black-oil PVT properties and compositional fluid were generated with an EOS model that have been tuned with experimental data. Black-oil model was tested against the fully compositional model in performing natural depletion scenario of gas-condensate reservoir. In addition, the composition of the fluid was varied to determine the limitation of black-oil model. The black-oil model proved to be adequate for gas-condensate reservoir simulation. Black-oil model is not suitable for history matching process in simulation if the liquid drop of the fluid is greater than 2%. Therefore, black-oil model may results major error in medium-to-rich gas-condensate reservoir simulation.